The empowering journey: Nepalese women transforming from margins to empowerment - Jati, Raju; Maharjan, Rumi (Group of Helping Hands, Nepal, 2023)
Nepalese women are facing increased burden in managing household chores and farming roles due to climate change and male outmigration, resulting in them being left behind in the development process. The situation is dire for poor and marginalized women, such as Dalits, who suffer the intersectionality of caste and gender-based discrimination, violence, educational disparities, lack of political participation, and are deprived of basic human rights and opportunities. In this context, SAHAS Nepal, an NGO, implemented a three-year gender-focused project of empowering and enhancing resilient food systems in a Dalit women’s group in the Dhading district, a mid-hill region of central Nepal. The project has led to the empowerment of the Dalit women’s group and promotion of climateresilient farming practices in them. This contributed to their transformative changes in building resilient and sustainable food systems and their socioeconomic empowerment, and more importantly in achieving dignity in society, thereby challenging existing inequities. Members of this group have been elected to local government positions and now have access to decision-making and government resources. This Dalit women’s group has emerged as role model for society and other communities. To examine the impact of the project and to explore the intricate details of the change process, a comprehensive qualitative study was conducted that included in-depth interviews and FGDs with members of the women’s group. The information was analyzed thematically to understand the socioeconomic transformation highlighting the journey of the women’s group. The study provides insights on women’s socioeconomic transformation, benefiting policymakers and development organizations.